Penerapan Standar Isi Pendidikan Dasar - Ananda, Rizki; Nur Fadia, Fenti; Dwi Putri, Irmania; Sari, Nurmala (Universitas Nusantara PGRI Kediri, 2024)
Basic education plays a key role in developing students' critical thinking skills in preparation for tackling complex global challenges. The purpose of this study was to analyze the application of basic educational content standards in basic education learning and its impact on improving students' critical thinking skills. This study utilizes methods of data collection processes conducted through literature reviews of scientific papers, as the data generated is descriptive. Data analysis was performed using a qualitative approach. Research results show that applying basic educational content standards to basic educational learning can significantly contribute to improving students' critical thinking skills. Primary school teachers who apply content standards extensively and consistently in primary education create learning environments in which students develop critical thinking skills through comprehension of content, analysis of information, evaluation of arguments, and rational decision-making. can be produced.